2013
DOI: 10.2967/jnumed.112.116699
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Quantitative Assessment of Pulmonary Blood Flow with 18F-FDG PET

Abstract: Pulmonary blood flow (PBF) is a critical determinant of oxygenation during acute lung injury (ALI). PET/CT with 18 F-FDG allows the assessment of both lung aeration and neutrophil inflammation as well as an estimation of the regional fraction of blood (FB) if compartmental modeling is used to quantify 18 F-FDG pulmonary uptake. The aim of this study was to validate the use of FB to assess PBF, with PET and compartmental modeling of 15 O-H 2 O kinetics as a reference method, in both control animals and animals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 33 publications
(36 reference statements)
1
9
0
Order By: Relevance
“…This discrepancy could be related to the underestimation of blood volume by Pouzot et al in consequence of their non-consideration of the delay, as shown in the current work, and supports the relevance of considering a delay for improved physiological description. Contrary to the suggestion of Pouzot et al that pulmonary transit times are homogeneous throughout the lungs, 26 regional pulmonary vascular delays in our study were highly heterogeneous, in agreement with numerous previous studies on the distributions of pulmonary capillary transit times. 3, 27, 40, 41 Overall, these findings suggest that while blood volume may be correlated with perfusion in most lung conditions, more accurate quantification of perfusion can be achieved by additionally accounting for regional transit times, according to Equation 4.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…This discrepancy could be related to the underestimation of blood volume by Pouzot et al in consequence of their non-consideration of the delay, as shown in the current work, and supports the relevance of considering a delay for improved physiological description. Contrary to the suggestion of Pouzot et al that pulmonary transit times are homogeneous throughout the lungs, 26 regional pulmonary vascular delays in our study were highly heterogeneous, in agreement with numerous previous studies on the distributions of pulmonary capillary transit times. 3, 27, 40, 41 Overall, these findings suggest that while blood volume may be correlated with perfusion in most lung conditions, more accurate quantification of perfusion can be achieved by additionally accounting for regional transit times, according to Equation 4.…”
Section: Discussionsupporting
confidence: 87%
“…Fuld et al also observed the presence of a positive intercept of blood volume for zero flow using CT-based measurements of pulmonary blood flow and blood volume. 10 In contrast, Pouzot et al found a negligible intercept when comparing 18 F-FDG derived blood volume with 15 O-H 2 O perfusion, 26 which is inconsistent with that physiological principle of mean circulatory filling pressure. This discrepancy could be related to the underestimation of blood volume by Pouzot et al in consequence of their non-consideration of the delay, as shown in the current work, and supports the relevance of considering a delay for improved physiological description.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations